The art of tinkering : meet 150+ makers working at the intersection of art, science and technology - Wilkinson, Karen; Petrich, Mike (San Francisco : Weldon Owen, 2013)
The Art of Tinkering is a collection of exhibits, artwork, and projects that celebrate a whole new way to learn, in which people create their own knowledge through making and doing, working with readily available materials, getting their hands dirty, collaborating with others, problem-solving in the most fun sense of the word, and, yes, oftentimes failing and bouncing back from getting stuck. Each artist featured in The Art of Tinkering goes through this process, and lovingly shares the backstory behind their own work so that readers can feel invited to join in on the whimsy. Whether it's sharing their favorite tools (who knew toenail clippers could be so handy?) or offering a glimpse of their workspaces (you'd be amazed how many electronics tools you can pack into one pantry!), the stories, lessons, and tips in The Art of Tinkering offer a fascinating portrait of today's maker scene. Artists include Scott Weaver, Arthur Ganson, Moxie, Tim Hunkin, AnnMarie Thomas, Ranjit Bhatnagar and Jie Qi.